One-Stop Shopping in Portugal - Manuel Leitão Marques, Maria (World Bank, Washington, DC, 2012)
In 2005, it took 11 procedures and 78 days to start a business in Portugal, making it slower than the Democratic Republic of Congo. An entrepreneur would need 20 forms and documents, more than for any other European Union (EU) country, and the total cost was 13.5 percent of the gross national income (GNI). As soon as new Prime Minister Jose Socrates took office in March of 2005, the planning for reform began, and in four months Empresa Na Hora (On the Spot Firm), the Portuguese one-stop shop for creating a company, was fully operational. Portugal is now one of the easiest countries to start a business in, taking only seven procedures, and the total cost has decreased to 3.4 percent of the GNI.